A place in public : women's rights in Meiji Japan - Anderson, Marnie S., 1975- (Harvard East Asian monographs, 2010)
This book addresses how gender became a defining category in the political and social modernization of Japan. During the early decades of the Meiji period (1868-1912), the Japanese encountered an idea with great currency in the West: that the social position of women reflected a country's level of civilization. Although elites initiated dialogue out of concern for their country's reputation internationally, the conversation soon moved to a new public sphere where individuals ranging from ordinary people to government officials engaged in a wide-ranging debate about women's roles and rights.